Effect of Flow Discharge on Sedimentation in Paneki River - Nina Bariroh Rustiati; Vera Wim Andiesse; Nadilla (Tadulako Science and Technology Journal, 2023)
Introduction: Paneki River has the potential for sedimentation caused by flow discharge. The condition of the river is getting wider every day which will threaten the risk of flooding if there is heavy rain with high intensity. The purpose of this study is to determine the return time flood discharge and basic sediment transport discharge in the Paneki river which can be used as a reference in planning sediment control buildings. Method: This research method includes primary data collection and secondary data collection, data management including calculating width, slope, design rainfall, design flood discharge, sieve analysis, and specific gravity. Then proceed to calculate the return time flood discharge using the Nakayasu synthetic unit hydrograph method and basic sediment transport using the Meyer-Peter and Muller method. Results and Discussion: From this research, the result of the 2-year return time flood discharge is 121.306 m3/det, for 5-year return time flood discharge is 185.069 m3 /det, for 10-year return time flood discharge is 209.261 m3 /det, for 25-year return time flood discharge is 312.359 m3 /det, and for 50-year return time flood discharge is 373.566 m3 /det. The results of basic sediment transport discharge per cross-section ranged from 0.0000861 m3 /det to 0.005641775 m3 /det. Conclusion: The study shows that sedimentation is influenced by flow discharge. The results of the calculation of flow discharge (Q) and bottom sediment transport (Qs) in Paneki River using the Meyer-Peter and Muller method resulted in Qs varying from 0.0000861 mÂ³/det to 0.016551197 mÂ³/det, according to the measured flow discharge. The greater the flow discharge, the greater the sediment transport, indicating a direct relationship between flow discharge and sedimentation.